Causes of Pruritus in Patients Treated With Immune Checkpoint Inhibitors for Melanomas or Skin Carcinomas - Salinas, Nadia; Nowak, Emmanuel; Etienne, Maxime; Legoupil, Delphine; Fouchard, Maxime; Brenaut, Emilie; Misery, Laurent (Frontiers in Medicine, 2021)
Background: Pruritus is a frequent adverse event during the use of immune checkpoint inhibitors (ICIs), with a frequency estimated to be between 11 and 47%. The underlying causes remain poorly understood. Objectives: The main goal was to search for putative causes of pruritus occurring in patients treated with ICIs for melanomas and cutaneous carcinomas. Other objectives were to assess the association between the occurrence of pruritus and survival and between the occurrence of pruritus and other adverse events. Methods: A monocentric retrospective descriptive study was performed using data for patients treated with ICIs (nivolumab, pembrolizumab, ipilimumab, cemiplimab) between August 2010 and November 2019. Results:A total of 181 patients were included (mean age: 69 years). Pruritus was reported by 25 patients (13.8%). We were able to determine three subgroups of pruritus causes under ICI use: pruritus directly related to immunotherapy, pruritus indirectly related through other pruritus-inducing side effects and pruritus unrelated to ICIs. In 6/25 patients, no more specific cause of pruritus was found at the onset of pruritus or in their backgrounds, other than ICI use. Limitations: The study has some limitations due to is unicentric and retrospective design. Conclusion: Pruritus was found in 25/181 patients in this series; only in 6/25 patients no potential cause other than ICI could be found, and pruritus was not associated with differences in survival.